Application of the Problem Based Learning Model: Efforts to Improve Student Learning Outcomes - Mazrur; Surawan; Sarifah, Siti (Journal for Lesson and Learning Studies, 2024)
The primary issue addressed in this study is the need for effective teaching strategies to enhance student learning outcomes, particularly in Fiqh subjects at madrasahs. This study aims to examine the effectiveness of implementing the Problem-Based Learning (PBL) model within the Merdeka Curriculum to improve student learning outcomes in madrasahs. The research employed a quantitative method, with participants comprising Fiqh teachers at Islamic Senior High Schools (MAN) and 10th-grade students in the religious studies program. Data were collected through observation, questionnaires, interviews, and documentation. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. The findings reveal that the application of the PBL model effectively enhances student learning outcomes. This is evidenced by the comparison of pre-test and post-test results. At the first MAN, the average pre-test score of 74.8% increased to 88.2% in the post-test, showing an improvement of 13.4%. Similarly, at the second MAN, the average pre-test score of 75.2% rose to 87.5% in the post-test, with an improvement of 12.3%. This study concludes that the Problem-Based Learning model is effective in enhancing Fiqh learning outcomes among 10th-grade students in Islamic Senior High Schools, while also contributing positively to the implementation of the Merdeka Curriculum.